The influence of the manager's leadership role on employee performance in the UMKM Flushartworks - M.Zidan Husaini; Nandang Nandang; Ghia Ghaida Kanita (Institute of Computer Science (IOCS), 2023)
Human Resource Management is one part of management where the main focus is on human roles, processes and activities to achieve an organizational goal. In the organization itself there are two roles, namely a manager or leader and an employee or employee. Both have different roles and responsibilities but are related to each other.This study aims to determine the influence of Leadership Roles on Employee Performance in Flushartworks SMEs which have been established since 2018, and are engaged in furniture services. Flushartworks provides a variety of custom furniture production services for the needs of households, schools, agencies or institutions and offices. Researchers take themes or topics related to human resource management where the focus of this research is on the role of leadership as a variable (x) and employee performance as a variable (y). Source This research uses quantitative approach method.The sampling used was using the purposive sampling method and obtained 6 samples. The data sources in this study used primary and secondary data. The analysis technique used uses a simple regression analyst method. The Result shown that managerial leadership has a contribution to the performance variable in Flushartwork by 58.4%. The leadership variable has a positive effect on performance.